2020
DOI: 10.1002/jbmr.4665
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Pathophysiology, and Genetics of Primary Hyperparathyroidism

Abstract: In this narrative review, we present data gathered over four decades on the epidemiology, pathophysiology and genetics of primary hyperparathyroidism (PHPT). PHPT is typically a disease of postmenopausal women, but its prevalence and incidence vary globally and depend on a number of factors, the most important being the availability to measure serum calcium and parathyroid hormone levels for screening. In the Western world, the change in presentation to asymptomatic PHPT is likely to occur, over time also, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 177 publications
(286 reference statements)
0
83
0
5
Order By: Relevance
“…Gene set enrichment comparative analysis of Def-Ts and Rep-Ts suggests the possibility of alternative etiologies for these tumors and supports the notion that oxyphil cells in either context are lineal descendants of chief cells. The differential expression in parathyroid tumors of genes associated with beta-amyloid signaling reveals a potential connection between the increased amyloid burden in aging adults ( 62 , 63 ) and the heightened incidence of PHPT among older individuals ( 64 ). Collectively, these findings suggest that PHPT in vitamin D-deficient patients may be a distinct subset of the disease with an alternative etiology, tumor composition, and cellular behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Gene set enrichment comparative analysis of Def-Ts and Rep-Ts suggests the possibility of alternative etiologies for these tumors and supports the notion that oxyphil cells in either context are lineal descendants of chief cells. The differential expression in parathyroid tumors of genes associated with beta-amyloid signaling reveals a potential connection between the increased amyloid burden in aging adults ( 62 , 63 ) and the heightened incidence of PHPT among older individuals ( 64 ). Collectively, these findings suggest that PHPT in vitamin D-deficient patients may be a distinct subset of the disease with an alternative etiology, tumor composition, and cellular behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In this prospective study evaluating 18 PHPT patients for neurocognitive disorders before and 1 month after successful parathyroidectomy, a follow-up over 6 months in 13 of these patients was completed. The baseline impaired neurocognitive functions were: [1] the short-and long-term verbal memory with learning abilities assessed by RAVLT, [2] the short-and long-term visual memory, attention, planning, and working memory assessed by ROCF test, [3] visual attention, mental flexibility, and executive functioning evaluated by TMTs, and [4] complex neurocognitive functions (attention, memory, fluency, language, and visuospatial functions) assessed by ACE-III tests. This study demonstrated that successful parathyroidectomy resulted in a significant improvement in short-and long-term verbal memory and learning abilities (ACE5, RAVLT8).…”
Section: Discussionmentioning
confidence: 99%
“…Primary hyperparathyroidism (PHPT), the most frequent cause of hypercalcemia, is a common disease with 0.86% prevalence in the USA, and is more frequent in post-menopausal women (3-4/1 female-male ratio) ( 1 ), whereas in different western Europe countries the prevalence varies but a similar pattern of increased incidence specifically in postmenopausal women is observed ( 2 ) Nowadays, PHPT is usually diagnosed by laboratory routine tests in asymptomatic patients, but classic symptoms include kidney-related symptoms such as nephrolithiasis (15-20% of PHPT patients) and bone-related symptoms (<2% of PHPT patients) ( 1 , 3 ). Non-classic symptoms include muscle weakness, fatigue, rheumatological, neuromuscular manifestations, and neurocognitive and psychiatric symptoms ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Low and intermittent doses of PTH exhibit anabolic effects on bone volume and microarchitecture. In contrast, a continued hypersecretion of PTH, such as that which occurs in primary hyperparathyroidism, leads to bone resorption [ 40 , 41 ]. Acting as an opponent of PTH, calcitonin reduces calcium concentrations in the blood, for example, due to the inhibition of bone suppression or the suppression of calcium release from the bone [ 42 ].…”
Section: The Contribution Of the Gut–bone Axis To Bone Metabolismmentioning
confidence: 99%